Criminal Responsibility for Perpetrators of Perjury and Giving False Information (Study Decision Number: 66/Pid.B/2023/PN Kla) - Veronica, Natasya Vi; Baharudin, Baharudin; Satria, Indah (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
A phenomenon that often occurs in court is that witnesses tend to lie or provide information that is incorrect or does not match the incident. There are also witnesses who give different information during the court hearing from the information given in the witness examination report. This action is called the crime of perjury. The crime of perjury is the crime of providing false information on oath, where the information is not true and contradicts the truth. Perjury is a criminal act of giving false information on oath where the statement is not true and contradicts the truth. It is called perjury because the witness who previously gave a statement at the court hearing was obliged to take an oath/promise according to his religion. The problem in this research is what is the position of false oaths and false statements in the criminal justice process and what is the criminal responsibility of perpetrators of false oaths and giving false statements based on (Study Decision Number 66/Pid.B/2023/PN KLA). The research method used in this research is a normative juridical approach and an empirical approach. This normative juridical approach is implemented by studying legal norms or rules, legal principles in theories/opinions of scholars and applicable laws and regulations. The Empirical Approach is an approach carried out through direct research on research objects by means of observation and interviews. The results of this research explain that the position of the oath is very important when giving testimony, witnesses must provide information that is in accordance with facts and reality, based on actual events. In this case, the witness may not add or subtract from the actual content of the statement. The point is you have to see for yourself, hear for yourself and experience for yourself. Apart from that, the information must not be based on stories, experiences, opinions, conjectures and influences from other people. Apart from that, witnesses must not lie when giving testimony just to gain personal gain. Then the responsibility of the perpetrator of the crime of perjury from the aspect of criminal responsibility has no justification or excuse so that the defendant was sentenced to prison for 2 (two) years and 6 (six) months by the panel of judges based on decision number: 66/Pid.B/2023/PN cl. The author's suggestion is for companies to have an evaluation system for employees. And you must be firm with employees so that no more employees dare to abuse their position. For the police to be more careful in handling a case, it is necessary to first investigate the report received so that similar actions do not occur. It was recommended to the judge to give a longer sentence, because this case was very detrimental to the company and the police, because the police had to investigate a case that did not actually occur.